Transitioning of protein substitutes in patients with phenylketonuria: a pilot study - Yilmaz Nas, Ozlem; Ashmore, Catherine; Evans, Sharon; Pinto, Alex; Daly, Anne; Yabanci Ayhan, Nurcan; MacDonald, Anita (Frontiers in Nutrition, 2025)
IntroductionIn phenylketonuria (PKU), there is limited information about transitioning between protein substitutes and the influencing factors, particularly in young children. This pilot study assessed the stepwise transition from second to third-stage protein substitutes in children with PKU, aged 3–5 years.MethodsDemographics, child behavior, maternal anxiety, and food neophobia scores were collected at baseline, mid-transition, and final assessment. Blood phenylalanine (Phe) was collected from 6 months pre-baseline to post-final assessment.ResultsTwelve children (n = 4 males, 33%, median age 3.2 years) participated. Sixty-seven percent (n = 8) transitioned to liquid amino acid-based protein substitute and 33% (n = 4) to glycomacropeptide (cGMP) powder. Forty-two percent (n = 5/12) had a smooth transition (Group 1, median 3.5 months), while the remaining faced difficulty (n = 3, 25%, Group 2), or failed full transition (n = 4, 33%, Group 3). In Groups 2 and 3, caregivers failed to follow instructions, demonstrating inconsistencies and child resistance. Group 2 children had significantly higher blood Phe levels (above 360 μmol/L), that was significantly higher than Groups 1 and 3 (p < 0.01), with Groups 1 and 3 maintaining blood Phe within target (p < 0.01). Higher maternal education and nursery/school attendance significantly influenced transition success (p < 0.05). No significant differences were found in child neophobia, maternal anxiety, or child behavior (p > 0.05). Mothers generally reported satisfaction with the stepwise transition process.ConclusionA stepwise transition to third-stage protein substitutes in PKU is effective, but is dependent on child metabolic control, parental education, and nursery/school support.